2016
DOI: 10.1038/srep39459
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary effectiveness of breast cancer screening among 1.22 million Chinese females and different cancer patterns between urban and rural women

Abstract: To determine the preliminary effectiveness of breast cancer screening among Chinese females, 1226714 women aged 35–69 years first received clinical breast examinations. Urban women with suspected cancer received mammography followed by breast ultrasound (BUS), while rural suspected women underwent BUS followed by mammography. After one-year follow-up, 223 and 431 breast cancers were detected among urban and rural women (respectively), with overall detection rates of 0.56/1000 and 0.52/1000. Higher detection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…In America, conventional mammography examination would be conducted for women aged 45–74 years every 1 or 2 years [ 80 , 81 ] and the Gail model was constructed based on women with annual screening [ 3 , 12 ]. However, routine screening was seldom conducted in Asian women [ 82 ]; many of the breast cancer patients could not be detected and resulted in a lower number of observed breast cancer than actually existed, resulting in a higher E/O ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In America, conventional mammography examination would be conducted for women aged 45–74 years every 1 or 2 years [ 80 , 81 ] and the Gail model was constructed based on women with annual screening [ 3 , 12 ]. However, routine screening was seldom conducted in Asian women [ 82 ]; many of the breast cancer patients could not be detected and resulted in a lower number of observed breast cancer than actually existed, resulting in a higher E/O ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Despite cancer being one of the leading causes of morbidity and mortality ( 1 ), current cancer screening participation rates are variable, both internationally ( 2 , 3 ) and in Australia ( 4 ). This variability is of concern, as it has been demonstrated that participating in organized cancer screening programs can identify cancer at an earlier stage, examples including bowel ( 5 , 6 ), breast ( 7 , 8 ), and cervical ( 9 , 10 ), allowing for earlier detection and thus intervention in a person’s disease trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Although breast screening guidelines usually recommend screening by MG from 40 years old, Chinese studies performed these screening programs for patients older than 30 years. 14 17 Although clinical breast examinations every 1 to 3 years with breast awareness are recommended for women aged between 25 to 40 years of age as an average risk screening approach, participants older than 35 years of age were included in the present study. 18 The effect of different age groups needs to be clarified by future, large, prospective studies.…”
Section: Discussionmentioning
confidence: 99%